Linguistic and Textual Characteristics of Film Audio Description in Uruguay - Álvarez Lamas, Soledad; Gorrostorrazo Babuglia, Mayte Victoria (Íkala, Revista de Lenguaje y Cultura, 2024)
In Uruguay, audio description is an emergent field of study, with no more than twenty Uruguayan films audio described thus far. Considering that audio description scripts are a new text type, it is relevant to know their most notable linguistic and textual characteristics in the case of Uruguayan cinema. This work is the result of an empirical research project focused on audio description in Uruguayan fiction films based on data obtained from a multimodal corpus created specifically for this study. This corpus is composed of eleven audio described Uruguayan fiction films and their corresponding audio description scripts. It was analyzed qualitatively and quantitatively using AntConc and MAXQDA software to describe linguistic and textual recurrences in audio description scripts. The quantitative analysis showed the presence of nouns and verbs as the most frequent word classes, the relatively low frequency of adjectives, and the predominant types of lexemes (those of perception, movement, proper names of characters, and body parts). The qualitative analysis revealed that the semantic fields of movement, perception, the emotional and mental states of characters, their characterization, and the designation and description of the setting stand out in these Uruguayan audio descriptions. This study may contribute both to research in audio description and to audio descriptor training and professional practice.